Impact of good corporate governance, free cash flow, and auditor quality on earning management - Neva Widya Romadhan; Azmi Fitriati; Hadi Pramono; Bima Cinintya Pratama (Jurnal Mantik, 2024)
This research aims to determine and analyze the influence of managerial ownership, institutional ownership, independent board of commissioners, audit committee, free cash flow, auditor quality on earnings management with company size as a control variable in the non-cyclical consumer sector. The dependent variables in this research are managerial ownership, institutional ownership, independent board of commissioners, audit committee, free cash flow, auditor quality and the control variable used in this research is company size. The population of this research is all non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The sample selection in this study usedpurposive samplingwith certain criteria to obtain a sample of 13 companies. The data used is secondary data sourced fromannual report, the data analysis technique uses multiple linear regression analysis. Based on the results of the analysis and research that has been carried out, managerial ownership has no effect on earnings management, institutional ownership has no effect on earnings management, the audit committee has a negative effect on earnings management, the independent board of commissioners has no effect on earnings management, free cash flow has a positive effect on earnings management. , auditor quality has no effect on earnings management, and finally company size has no effect on earnings management. The implication that can contribute to detecting or avoiding earnings management, the audit committee variable is able to reduce or detect earnings management, on the other hand the free cash flow variable is able to strengthen earnings management within the company.